Implementasi Penilaian Autentik pada Pembelajaran Tematik di Sekolah Dasar - Febriani, Riska (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2021)
As an educational institution that implements the 2013 curriculum, the school will directly apply the appropriate assessment, namely the Authentic assessment. The purpose of this study was to determine the implementation of Authentic Assessment on thematic subjects at the fifth grade of SDN 003 Sungai Salak, Tempuling District, this study used descriptive quantitative research methods. The result of the data analysis concluded that the implementation of authentic assessment in thematic learning in Class V SDN 003 Sungai Salak, Tempuling District was categorically as good.